Youtube : um canal para visibilidade e profusão da ciência e tecnologia do IFES - Monteiro, Flávia Carpanedo (2019)
The present dissertation set out to study how YouTube may be applied to increase visibility and profusion of Science and Technology developed by the academic community, especially the students, of Instituto Federal do Espírito Santo, with the purpose of showcasing how the institution benefits society in general. Thus, an audiovisual program to be posted on YouTube was created and delivered alongside an excecution plan. The research had a qualitative and applied nature, and the method used is action research, with exploratory phases of bibliographical survey, observation of similar materials on the internet and tests of tools for the accomplishment; problem formulation and hypotheses phases; and seminar with the stakeholders for product formulation and delivery. By doing so, we studied a new form of institutional positioning on the internet and on social media that would help both accountability matters on public funding of research and the building of a positive image for the institution, that reflects the work it develops. Cyberspace and leadeship of social media were studied (from the perspective of authors such as Castells, Lévy and Sodré); as well as the strategic dimension of organizational and public communication (Kunsch, Duarte e Martinuzzo); we also investigated the advantages of using YouTube as a tool for institutional and scientific visibility (Burgess, Green e Jenkins). In the end, we delivered the pilot program “Se liga no Ifes” (and its excecution plan) with the purpose of bringing information abou the institution in a casual style and also showing the organization’s most human facet, the one that thinks, smiles, builds scientific knowledge and is transformed by it